Hyperborea: The Arctic Myth of Contemporary Russian Radical Nationalists - Victor Shnirelman (Journal of Ethnology and Folkloristics)
After the disintegration of the Soviet Union Russians had to search for a new identity. This was viewed as an urgent task by ethnic Russian nationalists, who were dreaming of a ‘pure Russian country’, or at least of the privileged status of ethnic Russians within the Russian state. To mobilise people they picked up the obsolete Aryan myth rooted in both occult teachings and Nazi ideology and practice. I will analyse the main features of the contemporary Russian Aryan myth developed by radical Russian intellectuals. While rejecting medieval and more recent Russian history as one of oppression implemented by ‘aliens’, the advocates of the Aryan myth are searching for a Golden Age in earlier epochs. They divide history into two periods: initially the great Aryan civilisation and civilising activity successfully developed throughout the world, after which a period of decline began. An agent of this decline is identified as the Jews, or ‘Semites’, who deprived the Aryans of their great achievements and pushed them northwards. The Aryans are identified as the Slavs or Russians, who suffer from alien treachery and misdeeds. The myth seeks to replace former Marxism with racism and contributes to contemporary xenophobia.